The goose girl - Hale, Shannon (Bloomsbury, 2017)
On her way to marry a prince she's never met, Princess Anidori is betrayed by her guards and her lady-in-waiting and must become a goose girl to survive until she can reveal her true identity and reclaim the crown that is rightfully hers.